Studi Perbandingan Perencanaan Ketebalan Lapisan Perkerasan Bandara Antara Metode Grafis Korps Angkatan Darat AS dan Metode PCN-ACN Federal Aviation Administration (FAA) - Fistcar, Wawarisa Alnu; Sudarsono, Bambang; Widayat, Widayat; Herlambang, Andy Rahmadi (Department of Civil Engineering, Diponegoro University, 2024)
Airport pavement is designed following the US Corporation of Engineers method or better known as the California Bearing Ratio (CBR) method and the FAA (Federal Aviation Administration) method which issues regulations for calculating airport pavement structures, namely AC (Advisory Circular) 150_5320_6D which same as the method CBR. In 2021, the FAA issued a standard for calculating airport pavement structures, namely AC (Advisory Circular) 150_5320_6G which uses the FAARFIELD assistance program. The difference in pavement thickness is at most 7.6 cm, on the flexible pavement type base course. In the FAARFIELD Auxiliary Program, all aircraft loads are taken into account as a contributor to pavement damage indicated by the CDF value that can accommodate aircraft loads, in contrast to the graphical method where aircraft are converted to design aircraft. The thickness of the base course using the graphical method is greater than that of the FAARFIELD Assistance Program, this is because when performing calculations, the initial base course value is the minimum value based on the minimum base course table for the use of top foundation layer material (AC No.150_5320_6G). The thickness of the surface course pavement is the same according to FAA provisions for the critical thickness of the surface course which is 4 in or 102 mm.